Penerapan Program Dinamik dalam Menentukan Jalur Perjalanan Optimum dengan Prosedur Backward Recursive Equation - Anggela Elsa; Agatha Mariska Panjaitan; Tetty Natalia Sipayung (Journal on Education, 2023)
In general, in big cities there are many lanes and intersections and this certainly makes it difficult for someone to determine the optimal route. Problems between travel time and distance from the location of origin to the destination location can also affect the costs to be incurred. To solve this problem, applied research was carried out using the dynamic programming method with the aim of determining the route with the shortest distance that the campus bus could pass from Universitas Katolik Santo Thomas to the Rahmat International Wildlife Museum and Gallery. Dynamic Programming is a mathematical technique used to optimize decision-making processes in stages. In this case data collection for all routes uses Google Maps which is then represented in a network diagram using the Geogebra application which is then completed using a backward recursive equation procedure in several stages, starting from the destination location to the origin location. With this procedure, it was concluded that the shortest route taken from Universitas Katolik Santo Thomas to Rahmat Gallery and Wildlife Museum Medan is Rahmat International Wildlife Museum and Gallery ® J&K Barber Shop ® Grandika Hotel ® Ring Road Intersection ® Universitas Katolik Santo Thomas with a distance of 10,66 kilometers.